Occupational stress and the existing correlations with occupational accidents among health professionals: A qualitative approach - Lima, Lucas Alves de Oliveira; Campos, Adilson Gomes de; Alves, Ana Paula da Penha; Pessoa, Clelson Gomes da Silva; Andrade, Natalya Mirelly dos Santos; Rebello, Flávia Adriana Santos (Seven Editora, 2024)
The objective of this study was to analyze the association between occupational stress and occupational accidents among physicians and nurses at a public hospital in the city of Três Rios, Rio de Janeiro, Brazil. To this end, an exploratory research with a qualitative approach was carried out with 20 professionals, thus involving physicians, nurses and nursing technicians. Data collection involved the application of in-depth interviews, and the data were analyzed using the discourse analysis technique. As a result, it was found that occupational stress is associated with the occurrence of occupational accidents among employees. Stress particularly affects women over 30 years of age in a common-law relationship, due to the long workload, work pressure, inadequate infrastructure and interpersonal problems in hospitals. The study highlighted the complexity of occupational stress, influenced by unfavorable working conditions, task overload, and interpersonal tensions, affecting not only mental health, but also worker safety and the quality of patient care. Workplace accidents, such as stress-related cuts and falls, underline the need to mitigate stress to protect staff and patients, affecting both the physical and psychological health of workers. DOI:https://doi.org/10.56238/sevened2023.006-115